Restoration planning strategy of transmission system based on optimal energizing time of sectionalizing islands / Dian Najihah Abu Talib - Dian Najihah , Abu Talib (2019)
Total blackouts are rare events, but when it happens, it causes adverse impacts on the public, economy, and security. The significance of these impacts is dependent on the duration of the blackout. Therefore, speedy power system restoration is crucially important. One of the power system restorations planning strategy is via the ‘build-up’ approach. In this approach, a system is sectionalized into subsystems or islands for the purpose of parallel restoration prior to resynchronization. In order to speed up the resynchronization of the islands, each island should have similar restoration times. Based on this objective, this thesis proposes a strategy to determine islands that have similar restoration times. This will involve identifying set of transmission lines that should not be energized to create the islands. The strategy is based on the combination of heuristic initialization and discrete optimization methods, assisted by graph theory. The heuristic initialization is applied to determine a set of initial solution of the islands. The initial solution is important to guide the optimization methods in finding the optimal solution. There are two discrete optimization techniques used in this work, which are the Artificial Bee Colony algorithm and Evolutionary Programming. Modification and simplification using parallel processing are done for both methods to grossly search the optimal solution and to minimize the program running time, respectively. The graph theory is used to model the network of the system and to determine the reenergizing path. Restoration constraints considered in this strategy are black start generator availability, loadgeneration balance, and the maintenance of acceptable voltage magnitude within each island. Parallel processing is implemented together with the proposed strategy to minimize the program running time. The technique is validated using IEEE 39, 118-bus, 300-bus and practical European 89-bus systems. Simulations were done using MATLAB software. The proposed technique can find a solution with 11% faster energizing time compared to published results from previous studies before the resynchronization process between the islands can be conducted. In summary, the proposed strategy managed to achieve the optimum solution for larger and complex systems.